Speech Perception and Sound-Quality Rating with an Adaptive Nonlinear Frequency Compression Algorithm in Mandarin-Speaking Hearing Aid Users - Xu, Li; Voss, Solveig C.; Yang, Jing; Wang, Xianhui; Lu, Qian; Rehmann, Julia; Kuehnel, Volker; Qian, Jinyu (Journal of the American Academy of Audiology, 2020)
Background Mandarin Chinese has a rich repertoire of high-frequency speech sounds. This may pose a remarkable challenge to hearing-impaired listeners who speak Mandarin Chinese because of their high-frequency sloping hearing loss. An adaptive nonlinear frequency compression (adaptive NLFC) algorithm has been implemented in contemporary hearing aids to alleviate the problem.Purpose The present study examined the performance of speech perception and sound-quality rating in Mandarin-speaking hearing-impaired listeners using hearing aids fitted with adaptive NLFC (i.e., SoundRecover2 or SR2) at different parameter settings.Research Design Hearing-impaired listeners' phoneme detection thresholds, speech reception thresholds, and sound-quality ratings were collected with various SR2 settings.Study Sample The participants included 15 Mandarin-speaking adults aged 32 to 84 years old who had symmetric sloping severe-to-profound sensorineural hearing loss.Intervention The participants were fitted bilaterally with Phonak Naida V90-SP hearing aids.Data Collection and Analysis The outcome measures included phoneme detection threshold using the Mandarin Phonak Phoneme Perception test, speech reception threshold using the Mandarin hearing in noise test (M-HINT), and sound-quality ratings on human speech in quiet and noise, bird chirps, and music in quiet. For each test, five experimental settings were applied and compared: SR2-off, SR2-weak, SR2-default, SR2-strong 1, and SR2-strong 2.Results The results showed that listeners performed significantly better with SR2-strong 1 and SR2-strong 2 settings than with SR2-off or SR2-weak settings for speech reception threshold and phoneme detection threshold. However, no significant improvement was observed in sound-quality ratings among different settings.Conclusions These preliminary findings suggested that the adaptive NLFC algorithm provides perceptual benefit to Mandarin-speaking people with severe-to-profound hearing loss.
Keywords: hearing aids; Mandarin Chinese; nonlinear frequency compression; speech perception; sound quality